Analisis Pengaruh Ekspor dan Impor Terhadap Pertumbuhan Ekonomi Pendekatan Akuntansi Arus Dana yang Dimediasi Foreign Direct Investment di Indonesia Tahun 2019-2021 - Amanda Dyah Ayu Wulan Cahya; Rida Perwita Sari (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The purpose of this study was to determine and examine the effect of exports and imports before, during, and after the covid-19 outbreak on economic growth with an accounting approach to foreign direct investment mediated fund flows in indonesia. Quantitative approach with PLS analysis technique is used in this study. Secondary Data obtained from various official websites were used in this study. This study provides the results that exports and imports have a positive and significant influence on economic growth with the approach of accounting for the flow of funds mediated by foreign direct investment in Indonesia. This implies that exports and imports have an important role in economic growth approach to accounting for the flow of funds. Foreign direct investment plays an active role in mediating the relationship between exports and imports to economic growth. The declining value of exports, imports, and foreign direct investment during the pandemic also affected the decline in economic growth in Indonesia. Export activity needs to be increased so that economic growth also increases. Likewise with import activities, although imports are excessive trade balance deficit, imports also have some positive influence on economic growth such as by importing can meet domestic needs and open opportunities to attract investors to invest. For this reason, imports need to be controlled so that economic growth continues to increase.